Friksi Perdagangan dan Korelasinya Terhadap Karakteristik Perdagangan Pada Data Keuangan Berfrekuensi Tinggi Di Bursa Efek Indonesia - Nurhayati, Immas (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
The sources of trading friction are studied, robust empirical measures of friction are provided. Four distinct measures of trading friction are computed from transactions data for 200 IDX stocks. Each observation for a company is an average over the 245 daily observations.All friction measures are expressed as a percentage of the average price (mentioned as the proportional half spread). The degree to which the various measures of trading frictions are associated with each other and with trading characteristics of stocks is examined. All the total friction measures are strongly related to the same variables in the same way. For association of trading friction with trading characteristics, the independent variables are the log of the average daily dollar volume, the stock's, the log of the average closing price and the log of the average number of trades per day. Quoted, effective and traded half spread measures decrease in number of trades, average daily dollar volume and stock price, and these variables are statistically significant in Indonesian Stock Exchange.